Regional development in airlines and travel agents relationship. - Alamdari, Fariba (Elsevier, 2002)
On average, 17% of airline operating cost are attributed to distribution costs which are associated with commissions to travel agents, ticketing, credit card fees, CRS fees and promotion. In recent years, airlines in North America and in Europe have been questioning the role of travel agents in the distribution chain and renegotiating commission fee structures. As a result, some large agents have introduced a management fee philosophy where the clients, especially corporations, pay a fee to the travel agent in return for predetermined services. Such services include providing up-to-the minute reports on travel patterns of employees, effectiveness of travel policies, advice on complicated itineraries, etc. Such changes in airline and travel agent relationships initially started in the US and were followed by the European carriers. However, Asian carriers have been slow in following their US and European counterparts. This raises a number of questions: What are the barriers, if any for Asian carriers, to follow their counter parts in Europe and US? Would airlines in the three regions be able to bypass travel agents and sell directly to their customers? Would the customers prefer to go direct to airlines? Would there be a variation in the airlines, and agents, relationship in each region? This paper addresses these questions by analysing the distribution strategies of major carriers in the US, Europe and Asia. It also discusses the changing relationship between airlines and travel agents, and the trend towards direct selling by airlines in each region.
Keywords: Airline distribution; Travel agents; Commissions